1970
DOI: 10.3402/tellusa.v22i6.10277
|View full text |Cite
|
Sign up to set email alerts
|

Daily fluctuations of radioactive fallout particles in ground-level air

Abstract: Long-range 500 mb and 300 mb air trajectories were computed in an attempt to interpret the daily variation of the number of fallout particles in the ground-level air observed at Fayetteville (3eoN, 94"W), Arkansas, after a nuclear weapon was tested at Lop Nor (40"N, 9O"E), China, December 24, 1967. The dates of occurrence of peak concentrations of fallout particles generally coincided with (a) the arrival times of air masses at 500 mb and/or 300 mb after completing a cycle around the world, and (a) the passage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
1990
1990

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It was determined in the 1960's that debris injected into the atmosphere by Chinese nuclear test explosions circled the world in 3 to 4 weeks [6 -9], Chen et al [10] computed long-range 500 mb and 300 mb air trajectories in an attempt to interpret the daily variation of the number of fallout particles in the ground-level air observed at Fayetteville (36°N, 94°W), Arkansas, after a nuclear weapon was tested at Lop Nor (40 °N, 90Έ), China, on December 24, 1967. Their results indicated that the nuclear debris were circling the world in about 10 days and 17 days at the 300 mblevel and 500 mb-level, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It was determined in the 1960's that debris injected into the atmosphere by Chinese nuclear test explosions circled the world in 3 to 4 weeks [6 -9], Chen et al [10] computed long-range 500 mb and 300 mb air trajectories in an attempt to interpret the daily variation of the number of fallout particles in the ground-level air observed at Fayetteville (36°N, 94°W), Arkansas, after a nuclear weapon was tested at Lop Nor (40 °N, 90Έ), China, on December 24, 1967. Their results indicated that the nuclear debris were circling the world in about 10 days and 17 days at the 300 mblevel and 500 mb-level, respectively.…”
Section: Resultsmentioning
confidence: 99%